Penerapan Metode Belajar Bersama dalam Memahami Sistem Peredaran Darah Pada Pelajaran IPA Siswa SMP Negeri 2 Kampar Kiri Hilir - Pakpahan, Tiorma (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Learning science in junior high school students becomes a challenge for teachers themselves in order to provide understanding to students. The teacher provides examples and practices in real circumstances in generating a good understanding of the student. In the circulatory system lessons, students are still not optimally understand well. During this learning method used is the lecture method. The learning of the circulatory system when brought to the learning system together with discussion will be better results. Classroom methods were used in this study by applying class VIII students of SMP N 2 Kampar Kiri Hilir and the data were analyzed descriptively. The results showed that the acquisition of learning outcomes through learning together with Cycles I, II and III continue to increase understanding of describing the circulatory system and its relation to health. Attitudes and behaviors that are expected by the learning and application of methods of learning together more clearly achieved. Keywords: Co-learning method, circulatory system